Penguatan Kompetensi Pedagogik Guru melalui Penggunaan Dynamic Geometry Software dalam Pembelajaran Matematika - Silfanus Jelatu; Ricardus Jundu; Emilianus Jehadus; Fransiskus Nendi; Alberta Parinters Makur; Gabariela Purnama Ningsi; Lana Sugiarti (Universitas Mathla'ul Anwar Banten, 2020)
STRENGTHENING TEACHER PEDAGOGICAL COMPETENCIES THROUGH THE USE OF DYNAMIC GEOMETRY SOFTWARE IN MATHEMATICS LEARNING. The selection of strategies, methods, models, and media of appropriate mathematics learning is a form of implementation of a teacher's pedagogical competence. In the 2013 curriculum, the teacher not only sets a scientific approach as a reference in implementing the learning process but also demands innovation to accommodate the right media as well. The role of instructional media, especially dynamic media, is very important in learning mathematics in both elementary and junior high schools. The media was used to explain abstract mathematical problems to be concrete, motivate students, stimulate student learning activities, and help the effectiveness of the learning process. Technological devices such as computers are one of the tools that can be used as dynamic mathematics learning media. Mathematical learning collaboration with ICT devices has been widely carried out in urban and rural areas in Indonesia. Dynamic Geometry Software (DGS) in the form of GeoGebra is a learning medium specifically developed to facilitate the learning of geometry, algebra, and calculus. Therefore, this community service activity (PkM) is intended to strengthen the teacher's pedagogical competence through the use of dynamic learning media using Dynamic Geometry Software (DGS) in the form of GeoGebra in mathematics learning in junior high schools. This PkM aims to train teachers to be able to operate or create mathematics learning media assisted by DGS, especially in learning geometry to students. By making their own, teachers can add insight and increase creativity in making learning media. The supported subjects in these community service activities were junior high school mathematics teachers in Ruteng City. As for the results obtained after the PKM activities, the teachers can operate and create mathematics learning media using DGS in the form of GeoGebra.